The sum of first n, 2nn, 2n, and 3n3n terms of an AP is S1, S2S1, S2, and S3S3 respectively. Prove that S3=3(S2−S1).S3=3(S2−S1).
Answer:
-
We are told that
S1S1 = Sum of first nn terms
S2S2 = Sum of first 2n2n terms
S3S3 = Sum of first 3n3n terms
- We know that the sum of first nn terms of an AP is given by
Sn=n2(2a+(n−1)d),Sn=n2(2a+(n−1)d), where aa is the first term and nn is the number of terms in the AP.
Therefore, we have S1=n2(2a+(n−1)d)S2=2n2(2a+(2n−1)d)S3=3n2(2a+(3n−1)d) - Now, 3(S2−S1)=3(2n2(2a+(2n−1)d)−n2(2a+(n−1)d))=3n2(2(2a+(2n−1)d)−(2a+(n−1)d))=3n2(4a+4nd−2d)−(2a+nd−d))=3n2(4a+4nd−2d−2a−nd+d)=3n2(2a+3nd−d)=3n2(2a+(3n−1)d)=S3
- Thus, S3=3(S2−S1).